Op de snijtafel van de genderhistoricus. Androcentrisme in de historische demografie - Janssens, Angélique (TSEG - The Low Countries Journal of Social and Economic History, 2020)
This article presents a discussion and analysis of the way in which the concept of gender is applied as an analytical category in the field of historical demography. Gender as an analytical category was introduced in the 1980s to reveal the social and cultural constructions of gender and power, and the way in which these gender constructions worked to marginalise women as a social group as well as making them invisible in mainstream history writing. After so many years the question arises to what extent gender mainstreaming has taken place in the practice of history writing and whether it has successfully pushed out former androcentric historical practices. I ask this question relating to the field of historical demography, and I do this by tracing gendered perspectives in all articles published in The History of the Family. An International Quarterly in all issues in five volumes: 2008, 2020, 2012, 2014 and 2016. All empirical articles in these issues were examined on whether and how the concept of gender was used. More androcentric analytical practices would lead to perspectives in which women would be regarded merely as bodies, appearing in variables such as ‘age at marriage’, rather than as agents of change or social actors. These latter roles would be reserved for men. Results show that in a majority of the publications authors do make use of the concept of gender. However, a content analysis shows that many of these articles use gender as an equivalent for sex, a practice which takes us back to the old biological perspectives on the differences between men and women. Still, the content analysis also shows that a considerable number of studies do make use of gender as an analytical category, thereby greatly enhancing the richness and complexity of approaches in the field. These studies shows that using gender as an analytical category in historical demography reduces one-dimensional functionalist and economistic perspectives on important demographic phenomena in the past.